2010
DOI: 10.1007/s00464-010-1204-x
|View full text |Cite
|
Sign up to set email alerts
|

Robotic and laparoscopic total mesorectal excision for rectal cancer: a case-matched study

Abstract: For rectal cancer, RTME may be as feasible and safe as LTME in terms of technical and oncologic issues. Further prospective randomized trials are necessary for conclusions to be drawn concerning definite oncologic outcomes of robotic procedures for rectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
165
1
7

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(184 citation statements)
references
References 24 publications
11
165
1
7
Order By: Relevance
“…The authors concluded that robotic-assisted laparoscopic low anterior resection for rectal cancer is feasible in experienced hands and the technique may facilitate minimally invasive radical rectal surgery. The same group published 2 further case-matched reports with bigger series (Hellan et al, 2007;Baek et al, 2011) confirming their conclusion from the initial study. They particularly highlighted the low conversion rate with robotic assisted rectal surgery.…”
Section: Learning Curve In Robotic Rectal Surgerysupporting
confidence: 53%
“…The authors concluded that robotic-assisted laparoscopic low anterior resection for rectal cancer is feasible in experienced hands and the technique may facilitate minimally invasive radical rectal surgery. The same group published 2 further case-matched reports with bigger series (Hellan et al, 2007;Baek et al, 2011) confirming their conclusion from the initial study. They particularly highlighted the low conversion rate with robotic assisted rectal surgery.…”
Section: Learning Curve In Robotic Rectal Surgerysupporting
confidence: 53%
“…A number of reports have demonstrated a longer operation time with robotic surgery [9,[11][12][13], whereas others have reported no difference in operation time between robotic and laparoscopic surgeries [14][15][16][17][18]. Patriti et al reported a shorter operation time for robotic rectal resection; however, they are minority in this regard [19].…”
Section: Operation Timementioning
confidence: 99%
“…31 Most reports of robot-assisted rectal resection, however, have been based on limited numbers of patients. [32][33][34][35] A small prospective, comparative trial performed in Korean patients 36 compared laparoscopic to robotic-assisted low anterior resection. Although initially designed as a randomized study, the study had difficulty recruiting patients to accept randomization.…”
Section: Review Articlementioning
confidence: 99%